The NS1 protein of the parvovirus MVM Aids in the localization of the viral genome to cellular sites of DNA damage. - Kinjal Majumder; Maria Boftsi; Fawn B Whittle; Juexin Wang; Matthew S Fuller; Trupti Joshi; David J Pintel (PLoS Pathogens)
The autonomous parvovirus Minute Virus of Mice (MVM) localizes to cellular DNA damage sites to establish and sustain viral replication centers, which can be visualized by focal deposition of the essential MVM non-structural phosphoprotein NS1. How such foci are established remains unknown. Here, we show that NS1 localized to cellular sites of DNA damage independently of its ability to covalently bind the 5' end of the viral genome, or its consensus DNA binding sequence. Many of these sites were identical to those occupied by virus during infection. However, localization of the MVM genome to DNA damage sites occurred only when wild-type NS1, but not its DNA-binding mutant was expressed. Additionally, wild-type NS1, but not its DNA binding mutant, could localize a heterologous DNA molecule containing the NS1 binding sequence to DNA damage sites. These findings suggest that NS1 may function as a bridging molecule, helping the MVM genome localize to cellular DNA damage sites to facilitate ongoing virus replication.